Morphology controllable syntheses of micro- and nano-iron pyrite mono- and poly-crystals: a review. Issue 38 (29th March 2016) - Xian, Haiyang; Zhu, Jianxi; Liang, Xiaoliang; He, Hongping
Abstract : This review provides comprehensive information of the outline of current knowledge regarding the morphology controllable syntheses of micro- and nano-iron pyrite mono- and poly-crystals. Abstract : Synthesis of iron pyrite with defined morphology has long been actively pursued, due to the strong size and shape dependence of their chemical and physical properties. This review provides comprehensive information outlining current knowledge regarding the morphology controllable syntheses of micro- and nano-iron pyrite mono- and poly-crystals. The wet-chemical methods are summarized as the controllable syntheses, including the hydrothermal, solvothermal, hot-injection and heating-up methods, sulphidation and methods with other relatively high efficiencies. The present study reveals the discussion of relationship between the morphologies and major controlling factors, the temperature, precursor chemicals, solvents and surfactants. The existing challenges for future fine tuning of iron pyrite facets are also proposed for improving the performance of iron pyrite based materials.